The Effect Of Baby Massage On Sleep Quality And Weight Gain In Infants Aged 3-24 Months At The Ririn Pmb In Bengkulu City In 2025 - Sari, Hartini Saputri Endang; Syafrie, Ice Rakizah; Nurjanah, Nimas Ayu Lestari (Journal of Research in Social Science and Humanities, 2025)
Background: Globally, there are 149.2 million children under the age of 5 experiencing growth and developmental disorders (WHO, 2020). Important factors influencing infant growth and development include sleep quality and body weight. One safe and appropriate intervention for infants is baby massage (Fitriyanti, 2024). Baby massage is a gentle and rhythmic massage given to infants, starting with light touches and gradually increasing pressure according to the baby's age. This helps calm the nervous system and reduce stress hormone levels (Rahayu, 2020). Objective: To determine the effect of baby massage on sleep quality and weight gain in infants aged 3–24 months at PMB Ririn, Bengkulu City, in 2025. Method: This study used a pre-experimental design with a one-group pre-test and post-test approach. Data were collected using questionnaires, observation sheets, and growth monitoring charts (KMS). The study sample consisted of 20 infants selected through purposive sampling. Results: Before the intervention, most respondents had poor sleep quality (7 infants or 35%) and fair sleep quality (7 infants or 35%). After the baby massage intervention, most infants showed improvement to good sleep quality (16 infants or 80%). The average body weight before the intervention was 8,140 grams, which increased to an average of 8,875 grams after the intervention—an average gain of 735 grams per month. Bivariate analysis using the Wilcoxon signed-rank test showed that baby massage had a significant effect on improving both sleep quality and infant body weight, with a p-value of 0.000.